Revised M06 density functional for main-group and transition-metal chemistry - Wang, Ying; Verma, Pragya; Jin, Xinsheng; Truhlar, Donald G.; He, Xiao (Proceedings of the National Academy of Sciences - PNAS, 2018)
We present a hybrid metageneralized-gradient-approximation functional, revM06, which is based on adding Hartree–Fock exchange to the revM06-L functional form. Compared with the original M06 suite of density functionals, the resulting revM06 functional has significantly improved across-the-board accuracy for both main-group and transition-metal chemistry. The revM06 functional improves on the M06-2X functional for main-group and transition-metal bond energies, atomic excitation energies, isomerization energies of large molecules, molecular structures, and both weakly and strongly correlated atomic and molecular data, and it shows a clear improvement over M06 and M06-2X for non-covalent interactions, including smoother potential curves for rare-gas dimers. The revM06 functional also predicts more accurate results than M06 and M06-2X for most of the outside-the-training-set test sets examined in this study. Therefore, the revM06 functional is well-suited for a broad range of chemical applications for both main-group and transition-metal elements.